2018
DOI: 10.1177/0363546518782454
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in the KOOS Quality of Life Subscore Between Anatomic Double-Bundle and Anatomic Single-Bundle Anterior Cruciate Ligament Reconstruction of the Knee: A Prospective Randomized Controlled Trial With 2 Years’ Follow-up

Abstract: There was no difference in the KOOS QoL subscore, the remaining PROs, knee laxity measurements, or activity levels comparing the double- and single-bundle ACL reconstruction techniques. The number of bundles does not seem to influence clinical and subjective outcomes, as long as the tunnels are adequately positioned. Registration: NCT01033188 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 100 publications
(222 reference statements)
3
43
0
Order By: Relevance
“…The postoperative International Knee Documentation Committee (IKDC), Lysholm and Tegner scores were significantly improved in both groups compared to the pre-operative status (P < 0. (4)(5)(6)(7)(8)(9) in the DBR group. But there was no significant difference between the two groups (P > 0.05, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative International Knee Documentation Committee (IKDC), Lysholm and Tegner scores were significantly improved in both groups compared to the pre-operative status (P < 0. (4)(5)(6)(7)(8)(9) in the DBR group. But there was no significant difference between the two groups (P > 0.05, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This procedure has been reported to outperform SB reconstruction for better rotation stability of the knee joint and fewer graft failures 6 . However, several studies indicated that the number of bundles did not seem to influence clinical and subjective outcomes 7 , 8 . In addition, the drawbacks of DB reconstruction, such as extended operation time, high cost, increased risk of bone bridge fractures, and challenge in revision surgery, etc., also urge us to reconsider the necessity of this technique 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still controversial whether double-bundle or single-bundle reconstruction will provide superior clinical results. Previous studies revealed no significant difference in objective or subjective outcomes between the double-bundle and single-bundle reconstruction [5][6][7][8][9]. Conversely, several biomechanical and clinical studies have demonstrated that double-bundle reconstruction was superior to single-bundle reconstruction in restoring the knee joint's anterior and rotational stability [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies [14][15][16][17][18] have shown a comparison of excellence between SB-ACLR or DB-ACLR, but the results are still unclear, and quantitative analyses of biomechanical results are insufficient. Thus, the purpose of the present study was to perform a meta-analysis to compare the biomechanical outcomes of SB-ACLR versus DB-ACLR and determine their relative effectiveness in anterior tibial translation (ATT), internal rotation, or pivot in the setting of ACLR.…”
Section: Introductionmentioning
confidence: 99%